High Detection Rate Fast-Gated CMOS Single-Photon Avalanche Diode Module - Marco Renna; Alessandro Ruggeri; Mirko Sanzaro; Federica Villa; Franco Zappa; Alberto Tosi (IEEE Photonics Journal, 2020)
We present a novel instrument for fast-gated operation of a 50 μm CMOS SPAD (Complementary Metal-Oxide-Semiconductor Single-Photon Avalanche Diode), driven by an integrated fast-gated active quenching circuit with transition times faster than 300 ps (20–80%). The instrument is based on a custom system-in-package where the SPAD and its driving electronics are housed in a TO-8 package. The detector can be operated at repetition rates up to 160 MHz, with gate on-times as short as 500 ps, always guaranteeing a temporal response with 60 ps (FWHM) timing jitter and short exponential decay (53 ps time-constant). A dark-count rate as low as 1 cps is achieved operating the CMOS SPAD at 5 V above breakdown at a temperature of 263 K, still keeping the afterpulsing probability lower than 2%, with only 50 ns hold-off time, thanks to the fast-gating driving electronics. The instrument is housed in a compact 5 × 4 × 8 cm3 case and can be triggered by either an external or internal source. A USB link allows to adjust measurement parameters, SPAD bias voltage and operating temperature. The high re-configurability of the instrument and its state-of-the-art performance make it suitable for applications where high detection rates and low timing jitter are required.